Research on supply chain performance under digital background: A bibliometric review - Zeng Shihua; Sidah Idris; Jaratin Lily (International Journal Of Modern Education (IJMOE), 2024)
Supply chain digitalization improves the speed and accuracy of supply chain information processing and analysis, achieving real-time visibility to enhance the accuracy and timeliness of management and decision-making, enabling collaborative cooperation among suppliers, manufacturers, distributors, and logistics service providers, and Significantly enhancing the overall performance of the entire supply chain. Supply chain digitalization has emerged as a powerful instrument for augmenting supply chain performance, attracting considerable attention in relation to supply chain performance. In order to clarify the impact of supply chain digitalization on supply chain performance, as well as the related research frameworks and their evolution, we used 1690 papers from the Web of Science database from 2000-2023 as the data source and conducted quantitative and visual analysis using bibliometrics and visualization methods. This paper first analyzes the time series distribution of published papers, core authors, country distribution, keyword cooccurrence, and keyword clustering, and describes the research status, hotspots, and related research of supply chain digitalization and supply chain performance. Secondly, CiteSpace software is used for cluster analysis in this field. The research results illustrate the frontiers of supply chain digitization and supply chain performance research, and put forward research suggestions from five directions to provide theoretical and practical reference for future research.